PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MAHASISWA STIE MADANI BALIKPAPAN - ', Mardatillah (Fakultas Ekonomi Universitas Wisnuwardhana, 2016)
Abstract : Education is a social activity that enable people still existand improve. STIE Madani Balikpapan as an educational institutionneeds to pay attention to the service to students. Service as an importantelement that effects the quality of students satisfaction. Bottom lineservice is the supporting factor to service marketing activity of STIEMadani Balikpapan in order to improve the service quality to studentsof STIE Madani Balikpapan. The research objectives are able tofind out and analyze the effects of service quality which consists ofvariabels of tangibles, reliability, responsiveness, assurance, andempathy. Also to find out which variabel has the dominant effect.This is a descriptive quantitative research. The number of populationis 174 people while the sample is 64 using the Slovin formula withthe mistake average is 10%. This research uses multiple regressionanalysis with the validity and reliability test to test the questionnaireitems. The result of the research showed that there is a significanteffect between tangibles, reliability, responsiveness, assurance, andempathy to the student satisfaction in STIE Madani Balikpapan withthe percentage of 52,9%. The hypotheses test partially showed thatassurance has dominant effect with the value of t-count is 4,711 >2,002 with the significant 0,000 , 0,05.Keyword : Satisfaction, tangibles, reliability, responsiveness,assurance dan empathy